Kananaskis country’s road to coexistence: exploring expert perceptions of roadside bear viewing and management strategies - Pumphrey, Annie; Meletis, Zoë A. (Frontiers in Conservation Science, 2023)
In North America, bear viewing is becoming increasingly popular with visitors to parks and protected areas. In the face of heightened visitation pressures in parks, this demand for roadside bear viewing poses risks to humans and wildlife. One related challenge is the formation of "bear jams" - traffic congestion caused by people slowing down or stopping to view bears. We examined the gaps in our understanding of the human dimensions of roadside bear viewing using Peter Lougheed Provincial Park (PLPP) in Kananaskis, Alberta, Canada as a case study. To gain insight into management strategies, risks, and observed human behavior associated with roadside bear viewing, semi-structured interviews (n=22) roughly 20 minutes long were conducted with expert participants, including park staff members, non-profit organization employees, and biologists. More consistent messaging and better communication about respectable roadside bear viewing practices, including suggestions about particular methods and channels of communication, were highlighted by respondents. The results of this study suggest that a holistic and adaptive approach could mitigate the risks associated with roadside bear viewing while also balancing conservation and recreation goals. This study provides valuable human dimensions insights into roadside bear viewing and its management.